Potensi Medical Error Pada Pelaksanaan Tarif INA-CBG’s - Zaimatuddunia, Irma (Jurnal Spektrum Hukum PMIH UNTAG Semarang, 2024)
Health planning and financing is one of the factors that influences the occurrence of medical errors. Currently, the National Health Insurance system uses the INA-CBGs tariff, which means a package tariff for all components in the hospital related to medical and non-medical services. Hospital treatment rates often exceed the INA_CBG's tariff package, this causes hospitals to have to implement efficiency across lines, this is very risky because it can affect the quality of service when this efficiency includes things related to patients. So, based on these problems, the author conducted research with the aim of discussing the potential for medical errors in the implementation of INA CBG's rates. From the research results, it was discovered that medical error was a very important factor. Not all of the problems were caused by medical personnel at the hospital but rather there was intervention from management. One of the potential medical errors in INA-CBGs rates is the problem of inaccurate diagnosis, efficiency of medicines, medical devices and payments to health workers.